PENGARUH MODEL JIGSAW DENGAN PERMAINAN CROSSWORD PUZZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPS SISWA KELAS IV SDN KEPUH KIRIMAN 1 WARU - Fitria Handayani, Nur; Mahya Fanny, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of the jigsaw puzzle model and crossword puzzle game on critical thinking skills in social studies. This research was motivated by students' low critical thinking skills in social studies. During learning activities, students were less active because the teacher still used the lecture method. Consequently, students' critical thinking skills have not developed optimally. This study uses a Quasi-Experimental Design, specifically the Nonequivalent Control Group Design. The population in this study were fourth-grade students of SDN Kepuh Kiriman 1 Waru. The sample in this study was class IV-B as the experimental class and class IV-D as the control class. The sampling technique used was purposive sampling. This study is a quantitative research type with an experimental approach. Data collection techniques were critical thinking ability tests and observation of learning activities. Data analysis techniques used were prerequisite tests (normality tests and homogeneity tests) and hypothesis testing using t-tests. Based on the calculation results using SPSS, it shows that Sig. (2-tailed), the value obtained is <0.001. This explains that Ho is rejected, so H1 is accepted. Therefore, it can be concluded that there is a significant influence on critical thinking skills in the social studies subject of fourth-grade students.